1998
DOI: 10.1021/la971412x
|View full text |Cite
|
Sign up to set email alerts
|

Oriented Immobilization of Antibodies for Immunosensing

Abstract: The covalent coupling of antibody fragments to linkers embedded in a monolayer matrix of phosphatidylcholine and cholesterol was examined at the air-water interface by the means of a quartz crystal microbalance, QCM. Two linkers that bind the free thiols of the Fab′ fragment were investigated. The nonspecific binding of bovine serum albumin and the specific binding of antigen were also monitored with the QCM. Standardized radioimmunoassay was used to confirm the immunoreaction and determine binding parameters.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 47 publications
1
47
0
2
Order By: Relevance
“…However, using these conventional immobilization techniques, there is a lack of control in properly orienting the biomolecules, limiting the portion of available binding sites. An oriented immobilization of antibodies can be achieved by nonoriented physisorption of antibodies or covalent coupling of protein A followed by oriented adsorption of the antibody via the F ab domain [93,123,129] or a direct linkage of the antibody via thiol groups [130]. In this way, Göpel and co-workers achieved the arranged linkage of an antigen, a synthetic peptide of the mouth and claw epidemic virus, on an x-hydroxyundecanethiol monolayer [73,131,132].…”
Section: Piezoimmunosensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, using these conventional immobilization techniques, there is a lack of control in properly orienting the biomolecules, limiting the portion of available binding sites. An oriented immobilization of antibodies can be achieved by nonoriented physisorption of antibodies or covalent coupling of protein A followed by oriented adsorption of the antibody via the F ab domain [93,123,129] or a direct linkage of the antibody via thiol groups [130]. In this way, Göpel and co-workers achieved the arranged linkage of an antigen, a synthetic peptide of the mouth and claw epidemic virus, on an x-hydroxyundecanethiol monolayer [73,131,132].…”
Section: Piezoimmunosensorsmentioning
confidence: 99%
“…By means of Langmuir-Blodgett (LB) and Langmuir-Schäfer techniques, biofilms characterized by a high degree of molecular orientation were ob- tained. Based on the LB technique, Vikholm and co-workers successfully oriented antibodies on LB-lipid films with embedded linker lipids [130,133,134]. The major drawback of nonspecific adsorption at the transducer surface still remains and can only be minimized by improved immobilization techniques, but cannot be influenced by the transducer itself.…”
Section: Piezoimmunosensorsmentioning
confidence: 99%
“…Characterization of the immobilized antibodies is usually based on macroscopic methods such as quartz crystal microbalance (QCM) (Vikholm and Albers, 1998;Babacan et al, 2000;Fung and Wong, 2001), surface plasmon resonance (SPR) methods (Oh et al, 2003;Cui et al, 2003) and others (Shriver-Lake et al, 1997;Brogan et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Standard methods use protein surface groups, such as lysine, cysteins and (reduced) cystines [88], and (oxidized) carbohydrates [89,90] for either a directed immobilization at the surface or to attach a linker group including heterobifunctional linker [91], acrylic acid derivatives [67], biotin [74], and phenylboronic acid [92]. These reactive groups bind to surfaces activated with electrophiles such as NHS ester and epoxy groups (lysine, cysteine and reduced cystine), aldehydes (lysine), maleimide (cysteine and reduced cystine), amino groups (oxidized carbohydrates), and salicylhydroxamic acid (phenylboronic acid).…”
Section: Immobilization Strategies For Different Probesmentioning
confidence: 99%
“…Immobilization chemistry was successfully transferred to microarray applications such as the reaction with protein A and G at the Fc part of the antibody [104][105][106], the reaction at an oxidized carbohydrate site [83], and the use of antibody thiol groups [83,88] for a site-directed binding to the surface. Pavlinkova et al reported on a site-specific method for labeling antibodies using a photoinduced insertion of a azidoadenosine-biotin conjugate into the Fab' domain [93].…”
Section: Immobilization Strategies For Different Probesmentioning
confidence: 99%